Pelatihan perawatan dan perbaikan peralatan elektronik rumah tangga bagi Kelompok Tuna Daksa - Muhammad Ma’ruf Idris; Ridwansyah Ridwansyah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This training activity aimed to enable disabledparticipants to gain additional knowledge and abilities relatedto the field of electronics, especially repairs and maintenanceof household electronic equipment, which can be used as aprovision for independent living in the community. Thetraining process was performed using lecture anddemonstration methods as well as direct practice. After that,the mentoring program was conducted to evaluate theparticipants' ability to the material provided. As the evaluation,participants’ was given damaged household electronics to berepaired. The results of this training activity were that thetraining participants presented agreement statements with amean score of 4.20 from the four assessment criteria, includingthe competitiveness of human resources, application of scienceand technology, community values and implementation ofservice. In addition, questions about the entrepreneurial spiritgot a score of 4.11, an explanation of the work procedure bythe speaker is easy to understand (score 4.20) and the skillsacquired in this training are needed by the surroundingcommunity (score 4.40). Finally, the partner manager'sresponse to this activity was very positive. This activity wasalso beneficial for participants and partners. They hope thatthis activity will be continued in the following years with moreparticipants.